1975
DOI: 10.1113/jphysiol.1975.sp010980
|View full text |Cite
|
Sign up to set email alerts
|

The effect of duodenal infusion on the electromyogram of gastric muscle during activation and inhibition of gastric emptying.

Abstract: SUMMARY1. When the abomasum of the conscious calf is partially distended, rhythmic motility can readily be recorded from the e.m.g. of the smooth muscle of the fundus (body) and antrum.2. In gastric evacuation rhythmic contractions of the antrum are reinforced by both rhythmic and tonic fundic contractions.3. The output volume of the stomach can be directly correlated with e.m.g. activity.4. Intragastric fluid is usually emptied in gushes coinciding with a strong contraction of the antrum but fluid may be evac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 7 publications
5
20
0
Order By: Relevance
“…The precise mechanisms by which these effects are exerted are not well understood, but both nervous and hormonal/humoral links may be involved. In the case of the interactions between the duodenal receptors and gastric muscular effectors, the pathway(~) must be either via extrinsic nerves or be hormonal (Bell & Grivel 1975).…”
Section: The Physiological Backgroundmentioning
confidence: 99%
“…The precise mechanisms by which these effects are exerted are not well understood, but both nervous and hormonal/humoral links may be involved. In the case of the interactions between the duodenal receptors and gastric muscular effectors, the pathway(~) must be either via extrinsic nerves or be hormonal (Bell & Grivel 1975).…”
Section: The Physiological Backgroundmentioning
confidence: 99%
“…This result indicates that all three gastric functions are inhibited simultaneously. Since it has been shown that inhibition of action potentials of smooth muscle results from acid in the duodenum Grivel, 1975) and is associated with quiescence of the gastric body and antrum (Bell, 1978), then the reduction of gastric secretion to basal levels noted in the present observations may also reflect a similar inhibitory effect from duodenal acid receptors. When the duodenum is perfused with isotonic NaHCO3 the functions ofthe stomach are enhanced, the abomasum empties most of the test meal in 45 min, and gastric acid and pepsinogen secretion is increased by a factor of two to three compared to acid perfusion.…”
Section: Resultsmentioning
confidence: 59%
“…We have examined the triple response of gastric emptying, acid secretion, and pepsinogen secretion when the duodenum is perfused with either 60 mM-HCl, which is known to retard physiological processes in the stomach, and isotonic NaHCO3 which is known to enhance these processes (Bell & Mostaghni, 1975;Bell & Grivel, 1975;Bell & Watson, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…11 Gastric emptying is considered to be the result of a complex coordination between proximal stomach tonus and pylorusduodenal relaxations. [12][13][14] In order to assess the effects of sildenafil on small intestine contractile activity, we decided to investigate its effects on spontaneous and chemically stimulated motor behaviour of rat duodenal segments.…”
Section: Introductionmentioning
confidence: 99%